Breve relato histórico de la revista científica biomédica más representativa del Ecuador: la Revista de la Facultad de Ciencias Médicas (Quito) publicada desde 1932 - González Andrade, Fabricio (2017)
This is a brief essay of the oldest journal in Ecuador, in the scientific and medical field. This historical account talks about the current view of the scientific manuscripts in the world, the history of the journal, and the journal in our days. The FCM has published over the years the magazines entitled Archives of the Faculty of Medical Sciences, from the year 1932 to 1945; the Journal of the Faculty of Medical Sciences (Quito), continuation of the Archives of the Faculty of Medical Sciences, from 1950 to the present; the Journal of the Association of the School of Medicine published in two periods, from 1943 to 1950, and from 1962 to 1965; the Journal of Physiological Sciences, published in 1972; the Science Journal of the Graduate School Association, from 1991 to 1999; the Ecuadorian Journal of Public Health of the Higher Institute of Postgraduate in Health in 2005. The Journal of the Faculty of Medical Sciences is the organ of official dissemination of the scientific production of the FCM of the UCE. It seeks to promote better practice in medicine, biomedical research and the debate inhealth sciences. For this reason, the journal publishes scientific manuscripts and communications on clinical, educational and scientific aspects related to the medical sciences and health in general. It is indexed in the databases LILACS-BIREME, LATINDEX and IMBIOMED